Mapudungun, Interculturality and Inclusiveness in the Chilean Educational System - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2023)
Mapudungun is one of the heritages that defines the identity of the Mapuche people. Their survival over time is mainly due to the re-ethnification processes that have occurred in the last decade. However, it is necessary to follow the strategies briefly developed in this work, in order to maintain its validity and revitalization in the Chilean sociocultural context. A maintenance program for this indigenous language must have the proper state support to become a healthy and self-sufficient language. All this will allow the continuation of the way of life of its users, as well as the faithful reflection of their culture within the multicultural world.